KEEFEKTIFAN METODE PEMBELAJARAN KOOPERATIF TIPEGROUP INVESTIGATION PADA MATA KULIAH DOKKAI 3 (Penelitian Eksperimen Kuasi pada Mahasiswa Pendidikan Bahasa Jepang Angkatan 2016/2017 Kelas B) - Zahra, Rustianur Hanifah; Sinaga, Mangatur; Rahayu, Nana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The purpose of this research is to discover how the application result and respond of method Cooperative Learning type Group Investigation on students that are participate in dokkai 3 lesson. This research used the experimental method with the form of Pre-Experimental Design. More specifically, researchers used Pre-Experimental Design in the form of One Group Pretest-Posttest Design. The sample of this research was 31 university students and the research had been done in three meeting. The data collection technique used questionnaire and interview. The application of this method, half of the member of the group was active in this activity. The university students’s response in questionnaire showed, almost all of them (90.3%) aggred that this method were helpful and make them more easy to understand Japanese text. The reason for this are because the student read the Japanese text in group, and they felt less bored when reading long Japanese text. Beside, this method help the student to translate the Japanese text more faster and correctly because they’re doing the translate job together. And then, the students’s response according to interview is most of students became more excited to study by interacting, cooperating, and motivating one to another in a group to do their task.Key Words : Cooperative learning, group investigation, dokkai